Correlation of Anticancer Effects of 12 Iranian Herbs on Human breast Adenocarcinoma cells with antioxidant Properties - Hoshyar, Reyhane; Mostafavinia, Seyedeh Elham; Zarban, Asghar; Hassanpour, Mohammad; Partovfari, Mozhde; Taheri, Amir; Pouyan, Mohsen (Free Radicals and Antioxidants)
Introduction: Many of Medicinal plants have been investigated for possible anticancer properties. The correlation cytotoxic effect of herbs with antioxidant activity is unclear, yet. The aim of the present study was to examine the antioxidant contents and anticancer effects of 12 Iranian medicinal plants on proliferation of breast cancer, MCF-7, and epithelial normal, MCf-10A, cells. Methods: Free radical scavenging and total antioxidant capacities of herbal waters assessed by DPPH and FRAP methods, respectively. Their total phenolic contents and cell viability determined by Folin–Ciocalteu and MTT assays, respectively. Results: Among the herbs, group A which contained relatively highest total phenolics content, antioxidant and free radical scavenging activities inhibited significantly greater growth of breast cancer cells in a dose- and time-dependent manner as compared to other groups. These medicinal plants were not cytotoxic components against normal cells. Conclusion: Therefore our results indicated that anti proliferative effects of 12 selected Iranian herbs showed a direct correlation with antioxidant properties. The herbs as natural antioxidants with fewer side effects could potentially improve the outcome of human breast cancer therapy. These findings endorse further investigations on these plants to determine their active metabolites and mode of action.
Keywords: Anticancer; Antioxidant; MCF-7 cells; MCF-10A cells; Herbs